Constituents of an Extract of Cryptocarya rubra Housed in a Repository with Cytotoxic and Glucose Transport Inhibitory Effects# - Ren, Yulin (2013)
A new alkylated chalcone (1), a new 1,16-hexadecanediol diester (2), and eight known compounds, were isolated from a dichloromethane-soluble repository extract of the leaves and twigs of Cryptocarya rubra collected in Hawaii. The structures of the new compounds were determined by interpretation of their spectroscopic data, and the absolute configurations of the two known cryptocaryanone-type flavonoid dimers, (+)-bicaryanone A (3) and (+)-chalcocaryanone C (4), were ascertained by analysis of their electronic circular dichroism and NOESY NMR spectra. All compounds isolated were evaluated against HT-29 human colon cancer cells, and, of these, (+)-cryptocaryone (5) was found to be potently cytotoxic toward this cancer cell line, with an IC(50) value of 0.32 µM. This compound also exhibited glucose transport inhibitory activity when tested in a glucose uptake assay.